Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1100/2012/793420
|View full text |Cite
|
Sign up to set email alerts
|

Natural Interactions betweenS. haematobiumandS. guineensisin the Republic of Benin

Abstract: Schistosomiasis is a parasitic disease which affects millions of people around the world, particularly in Africa. In this continent, different species are able to interbreed, likeSchistosoma haematobiumandSchistosoma guineensis, two schistosome species infecting humans. The Republic of Benin is known to harborS. haematobium, but its geographical situation in between Nigeria, Mali, and Burkina Faso, whereS. gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
1
27
1
3
Order By: Relevance
“…To our knowledge, S. intercalatum has never been reported in Benin, whereas S. guineensis was mentioned in only one publication. 26 A similar case-of uncertain diagnosis-was described in Gabon in 2005 by N'Dong and others, but the authors concluded to a S. haematobium lung disease considering epidemiological, pathophysiological, and morphological criteria, in the absence of molecular study and despite the positive ZiehlNeelsen stain. 27 Ultimately, the possibility of a hybrid species involvement such as S. haematobium/S.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…To our knowledge, S. intercalatum has never been reported in Benin, whereas S. guineensis was mentioned in only one publication. 26 A similar case-of uncertain diagnosis-was described in Gabon in 2005 by N'Dong and others, but the authors concluded to a S. haematobium lung disease considering epidemiological, pathophysiological, and morphological criteria, in the absence of molecular study and despite the positive ZiehlNeelsen stain. 27 Ultimately, the possibility of a hybrid species involvement such as S. haematobium/S.…”
Section: Discussionmentioning
confidence: 82%
“…30 Furthermore, interestingly, the molecular evidence of hybridization between S. haematobium and S. guineensis was described for the first time in Benin in 2012. 26 In conclusion, this case is remarkable for the rarity of pulmonary schistosomiasis, its peculiar clinical presentation, and the difficulty to identify the species. Because the exact genetic nature of the eggs was not determined, we cannot exclude the possibility of an infection with S. intercalatum (never reported in Benin) or with a hybrid species such as S. haematobium/S.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We suspect this phenomenon is more common than generally reported but evidence of this exists for only a few trematode taxa (e.g. Mone et al, 2012;Diaz et al, 2015).…”
Section: Sequencingmentioning
confidence: 79%
“…haematobium x S . guineensis [33,34], between schistosome species infecting animals ( S . bovis x S .…”
Section: Discussionmentioning
confidence: 99%